On Returning Inflation to Target - Catherine L. Mann; Lennart Brandt (Intereconomics, 2022)
To gauge the breadth of current inflation and prospects for inflation returning to target, we consider disaggregated measures of CPI infl ation to evaluate trends and then consider diff erent scenarios for the realisation for wages and prices.
Keywords: E31; E52; 330